Aporte al conocimiento del tamaño de camada de storeria storerioides (cope, 1865) y thamnophis pulchrilatus (cope, 1884) en el Distrito Federal, México - García-Vázquez, Uri Omar; Mendoza-Hernández, Andrés Alberto; Solano-Zavaleta, Israel (Instituto de Ecología, A.C., 2012)
We present information about clutch size and offspring size of Storeria storerioides and Thamnophis pulchrilatus. The clutch size herein reported of S. storerioides is different to other reports in the literature; additionally we present the first data about the clutch size and offspring size of T. pulchrilatus.